Adult-onset multifocal kaposiform hemangioendothelioma in the bone marrow, lung, liver, and brain: a case report - Bello, Alexa; Alikhan, Mir B.; Subramaniam, Aparna; Yusuf, Zenab I.; Brockstein, Bruce; Ravi, Vinod (Frontiers in Oncology, 2024)
Kaposiform Hemangioendothelioma (KHE), a rare form of vascular neoplasm, is typically seen in children. Here we report a unique case of KHE replacing bone marrow tissue mimicking myeloproliferative neoplasm with additional involvement in the lung, liver and brain in a 60-year-old Caucasian female. The patient was initially seen in the hematology department for chief complaint of epigastric pain and anemia. An abdominal magnetic resonance imaging (MRI) revealed mild splenomegaly with iron deposition secondary to extramedullary hematopoiesis. Additional workup was inconclusive. Subsequent bone marrow and lung biopsies eventually revealed bone marrow with extensive grade 3 fibrosis and multiple foci of low grade vasoformative neoplasm in the lung suggestive of Kaposiform hemangioendothelioma. Although rare, KHE can present as an aggressive disease with indolent behavior in adults and can be distinguished from other vascular malignancies based on histopathology and imaging findings.